Russian Federation : Selected Issues Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This note focuses on Russia's monetary policy, which is moving toward low and stable inflation. This paper discusses two analytical measures to analyze the monetary policy-core inflation measure and a group of leading indicators model (LIM). The trimmed mean core inflation is a good indicator for analyzing trend inflation and can be used as a viable target for monetary policy. LIMs are widely used for inflation forecasting and are also useful in detecting turning points in inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet